Spontaneous intramural rupture and intramural haematoma of the oesophagus. - Kerr, W F (1980)
Spontaneous intramural rupture or intramural haematoma of the oesophagus is a rare cause of acute pain in the chest and upper abdomen. Much less ominous than spontaneous complete rupture from which it must be distinguished, it seldom if ever necessitates operation. Five new cases are described and reviewed together with 15 collected from published reports. The dominant symptom of every case was severe and constant retrosternal or epigastric pain; concomitant dysphagia was mentioned in 11 cases. In seven the pain was preceded by or coincided with vomiting. The condition was related to other stresses in three and appeared to be truly spontaneous in 10. In approximately one-third of cases it started suddenly but more often it began as discomfort worsening rapidly. Fourteen patients vomited blood after experiencing pain but only four were given transfusions. In contradistinction to complete rupture, none had surgical emphysema and plain chest radiographs were unremarkable. All had abnormal gastrografin or barium swallows. Intramural haematomas with or without mucosal tears were seen in the 11 cases in which oesophagoscopy was performed. Fifteen patients made rapid and complete recoveries on conservative management. Of the four who did not respond satisfactorily, one had the oesophagus repaired, two had drainage of the mediastinum after failure to find the false lumen at thoracotomy, and one had only an abdominal exploration. The only death in the whole series occurred after a disastrous emergency exploration and subsequent total oesophagectomy.